Problems of early clinical diagnostics of pseudoexfoliation syndrome - A. Yu. Brezhnev; N. I. Kurysheva; V. N. Trubilin; V. I. Baranov (Oftalʹmologiâ)
Purpose: to study the informativeness of pseudoexfoliation syndrome (PES) signs for early diagnosis improvement.Methods: 250 patients with PES were included in the study. Exclusion criteria consisted of aphakia, pseudophakia, previous eye surgery and diseases which can complicate PES diagnostics (uveitis, corneal pathology, ocular injury etc.). Each patient underwent complete ophthalmic examination, including slit-lamp examination under mydriasis, gonioscopy. Confocal microscopy was used as an additional diagnostic method in several patients (Confoscan-4, Nidek).Results: Pseudoexfoliation material was found at the pupillary margin in 64.8% of patients, and on the lens capsule (central disc) in 71% of the test subjects. Peripheral depositions were present in almost all PES patients under mydriasis. Pupil dilation has been allowed to establish the diagnosis of PES additionally in 16% of patients. At the «mini-PES»-stage PES material was most frequently found in the superior-nasal quadrant of lens capsule (85.6%). Clinical asymmetry of several signs (pupil diameter, anterior chamber angle pigmentation, IOP level) should be taken into consideration in early PES diagnostics.Conclusion: Examination under mydriasis and knowledge of PES micro-signs in some cases has been allowed to suspect PESeven at the preclinical stage.